Distribution, biology and status of population of Neogobius Melanostomus legs and thriver (Zosterisessor Ophiocephalus) in Shabolatsky liman - Burgaz, Marina (ScienceRise: Biological Science, 2017)
There was studied the modern condition of populations of main industrial species of goby fish in Shabolatsky liman. The ecological catastrophe took place in 1992. As a result of the global suffocation, mass death of bottom fish (especially, gobies) was observed in the Southern-Western part of the water body. In the further period the ecological condition of Shabolotsky liman worsened because of the limited link with the sea. Several physical-chemical parameters of the water environment changed: salinity increased, organic content in water and bottom sediments grew, transparency decreased. The oxygen content in the near-bottom horizon decreased, hydrogen sulfide emissions were observed. The anthropogenic transformation of the liman ecosystem influenced qualitative and quantitative indicators of main groups of hydrobionts. The biological diversity and biomass of animal plankton and zoobenthos decreased, associations of macrophytes disappeared, the bloom of liman was observed the whole year round as a result of the progressing euthrophication. The renewal of the liman ecosystem took place only in 1997-2003. The reconstruction and continuous work of channels that connect Shabolatsky and Dnestrovsky limans and the regular work of a maritime channel provided normalization of the hydrologic-hydrochemical regime, restoration of biocenoses and forage reserve. The anthropogenic transformation of the ecosystem of Shabolatsky liman was reflected on population characteristics of melanostomus legs and thriver – the most mass species of neogobius in the liman. Their distribution in the liman water area, age and size-mass structure of populations, fatness, reproduction effectiveness and nutrition features changed. Most of these indicators differ from the previous period today. Along with it the received characteristics of neogobius melanostomus legs and thriver testify to the fact that their population in Shabolatsky liman is gradually renewed last years and its condition essentially improves